Paddy field quality and precision agriculture at moderate scale - LIU Xing-mei; ZHANG Wei-wen (浙江大学学报. 农业与生命科学版)
In this study, GIS and geostatistics technology were applied to analyze the spatial variability of soil organic matter, total nitrogen, available phosphorous and available potassium in paddy field in Pinghu County. Meanwhile, the spatial patterns of four soil properties were generated by ordinary kriging. Paddy field is widely distributed in the southeast region of China. Its particular cultivation fashion and growing condition make the variation of paddy soil differ from that of other soil. Besides of putting new insight into precision agricultural management, understanding the spatial distribution of soil nutrients is necessary for increasing the efficiency of applied fertilizers and decreasing the water pollution caused by the downward movement of unused fertilizer in the overfertilized area.